Effectiveness of resistance training of masticatory muscles for patients with temporomandibular disorders: protocol for a systematic review - Deborah Falla; Filippo Maselli; Giacomo Asquini; Andrea Giusti; Giulia Pisacane; Giovanni Galeoto; Firas Mourad; Paolo Bizzarri; Edoardo Balli; Cecilia Bagnoli; Anna Manzari; Marco Pernici (BMJ Open)
Introduction Temporomandibular disorders (TMDs) are musculoskeletal disorders characterised by jaw pain and typically temporomandibular joint limitations. Resistance training (RT) has been shown to be effective at reducing pain and improving function for different musculoskeletal conditions (eg, neck pain, low back pain); however, the effectiveness of RT for patients with TMDs remains unclear. This systematic review will evaluate the effectiveness of RT on pain and temporomandibular joint range of motion in people with TMDs.Methods and analysis The report of this protocol aligns with the Preferred Reporting Items for Systematic Reviews and Meta-Analysis Protocols. The search strategy will be conducted from 1 March 2024 to 31 March 2024 via the following electronic databases: MEDLINE (OVID interface), EMBASE (OVID interface), SCOPUS, Web of Science, PubMed and Cochrane Central Register of Controlled Trials. Any randomised controlled trials or non-randomised studies of interventions in adults with TMD that examine RT targeting the masticatory muscles, compared to other interventions not including RT, will be included. Primary outcomes will be jaw pain intensity and maximal mouth opening. Secondary outcomes will include measures of neuromuscular performance and pressure pain thresholds. Two independent reviewers will conduct the screening of articles for inclusion, data extraction, risk-of-bias assessment using the revised Cochrane risk-of-bias tool for included studies and will evaluate the overall quality of evidence following the Grading of Recommendations Assessment, Development and Evaluation framework. A meta-analysis will be performed where applicable. Alternately, a narrative synthesis will be performed by adhering to the synthesis without meta-analysis guidelines. Data will be summarised according to the outcome measures or, when this is not possible, according to other pertinent variables such as TMD type (ie, temporomandibular joint disorders, masticatory muscle disorders and mixed disorders).Ethics and dissemination Ethical approval is not necessary, since this study does not involve the collection of primary data. The results will be disseminated through presentations at scientific conferences and publication in a peer-reviewed journal.PROSPERO registration number CRD42023476269.